Studi Literatur: Optimasi Algoritma Machine Learning Untuk Prediksi Penerimaan Mahasiswa Pascasarjana - Zuhri, Burhanudin; Harani, Nisa Hanum (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2024)
Machine learning algorithms are mathematical procedures used to find complex and hidden patterns in data with a high degree of accuracy and have brought major advances in various fields for fast and precise decision making. One of these fields is the field of education, which is to predict the admissions process for postgraduate students. The purpose of admitting postgraduate students is to select prospective students who are qualified and meet the academic requirements set by the institution concerned based on GRE (Graduate Record Examination) scores, TOEFL (Test of English as a Foreign Language) scores, university rankings, letters of recommendation, GPA bachelor degree, and research experience. Success in postgraduate admissions can open opportunities to earn advanced degrees and acquire more in-depth knowledge and skills in areas of interest. In this study, an analysis was carried out on various machine learning algorithm optimizations used to optimize topics or trends in previous studies. In this case, the researcher compares performance and selects the best algorithm optimization to be applied to the topic of graduate student admissions. The results of this review show that the hybrid algorithm has the best performance in optimizing predictions for most of the data in previous studies. The results of this study indicate that the CNN-LSTM (Convolutional Neural Network - Long Short-Term Memory) hybrid model is expected to be an appropriate alternative in optimizing predictions of postgraduate student admissions. Therefore, further research is needed to develop this algorithm and expand its application to the topic of graduate student admissions.